Analisis Frasa Nominal Subordinatif pada Teks Berita Suara.Com “Tak Semuanya Sehat, Sayuran Jenis Ini Justru Picu Tekanan Darah Tinggi” - Risma Tiyasti Ningrum; Asep Purwo Yudi Utomo (Balai Bahasa Sumatera Utara, 2021)
Subordinate nominal phrases are a collection or consist of two or more words whose two elements are not equal. Some have a position as the superior element or core of the phrase, and who have a position as subordinate elements or are referred to as additional explanatory phrases. This article aims to find out the subordinative nominal phrase contained in the Suara.com news text entitled